SISTEM INFORMASI GEOGRAFIS (SIG) FASILITAS KESEHATAN DI KABUPATEN BUNGO BERBASIS MOBILE - Silvia Tauriska P; Muhammad Adri; Titi Sriwahyuni (Universitas Negeri Padang, 2016)
The information technology is developed to helping people to work mainly in obtaining information, including geographic information. The use of mobile technology is the most used technology to meet the needs of information including health information. Not all of health facilities have an information system, so people need energy and time to get the information. The use of information system and mobile technology can solve the problem. The use of geographic information systems and mobile in the field of health is building a search application health facilities. This technology system is proposed to produce a mobile application with the android operating system, based client server, visualization modelling UML. Implementation of this application using the programming language PHP with Code Igniter framework and MySQL as a Database Management System (DBMS). Mobile application is build using Java programming language with Eclipse. This application based on client server, so user must be connected to the internet to access it. This application can help the Bungo’s people to search and select health facilities. Keyword: Geographic Information, Health Facilities, Client Server, MySQL, Framework Codeigniter, Java, Eclipse, Mobile Application, Android, Online.